(FeNiMnCrV) Nx multilayer structure hydrogen-resistant coating with skin-like structure and preparation method of (FeNiMnCrV) Nx multilayer structure hydrogen-resistant coating
By applying a skin-like (FeNiMnCrV)Nx multi-layer structure hydrogen-resistance coating on hydrogen transport pipelines, using the multi-layer structure and interlayer interface to capture hydrogen atoms, the existing coating has low density and insufficient hydrogen resistance performance. The problem is that the safety of hydrogen transmission pipelines and the density of coatings are significantly improved.
Patent Information
- Application Number
- CN202411574371.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing composite hydrogen-retardant coating has low density, many defects, insufficient hydrogen-retardant performance, and is difficult to achieve large-scale industrial application, and cannot effectively prevent hydrogen embrittlement and improve the service safety of hydrogen transport pipelines.
Using a skin-like structure (FeNiMnCrV)Nx multi-layer structure hydrogen-resistance coating, the FeNiMnCrV sputtering layer, CrN intermediate layer, (FeNiMnCrV)Nx-CrN cyclic layer is deposited on the surface of the matrix material through a multi-arc magnetic filter cathode vacuum arc system and (FeNiMnCrV)Nx capping layer uses the characteristics of the interlayer interface and crystal structure to capture hydrogen atoms, improving the density and hydrogen resistance of the coating.
It significantly improves the service safety of hydrogen transport pipelines, reduces hydrogen permeability, enhances the density and hydrogen resistance of the coating, increases the hydrogen permeability time by nearly 103 times, and achieves more uniform coating preparation and lower Preparation cost.
Smart Images

Figure CN119194356A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen damage prevention of hydrogen transmission pipelines, and in particular to a method for preparing a skin-like (FeNiMnCrV)Nx multilayer structural hydrogen barrier coating. Background Art
[0002] With the development of green energy in recent years, especially the development of hydrogen energy, the use of hydrogen energy is increasing. The research and construction of long-distance hydrogen pipelines in my country is in its infancy. As we all know, hydrogen is always prone to hydrogen embrittlement in steel pipelines, leading to pipeline failure and damage, and even explosion accidents. Therefore, preventing hydrogen damage and improving the safety of hydrogen transmission and transportation have become key issues in the research of hydrogen pipelines, and hydrogen barrier coatings have emerged.
[0003] Studies have shown that composite coatings with hydrogen barrier / hydrogen storage functions have good hydrogen barrier properties. The interfaces between different layers can act as traps to capture hydrogen to a certain extent, and the dangling bonds in the coating can also improve the hydrogen barrier properties of the coating to a certain extent, which makes composite coatings a research hotspot. However, the existing composite hydrogen barrier coating preparation methods include plasma spraying, embedded aluminum diffusion, sol-gel method, and magnetron sputtering. The prepared coatings have a series of problems such as low density, many defects, and uneven particle size distribution, which leads to the limited hydrogen barrier effect of the prepared coatings. In addition, the preparation process is too complicated, and the thickness of the coating is difficult to control, so it is difficult to achieve large-scale industrial application of composite coatings.
[0004] Therefore, in response to the hydrogen embrittlement problem currently faced by hydrogen pipelines, the field urgently needs to develop a coating with high density, few defects and good hydrogen barrier properties, so as to overcome the shortcomings of existing coatings such as low density, many defects and weak hydrogen barrier properties, and improve the service safety of hydrogen pipelines. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a skin-like structure (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating. The (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating provided by the present invention has high density, few defects, and strong hydrogen barrier performance, which can greatly improve the service safety of hydrogen pipelines.
[0006] The second object of the present invention is to provide a method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating with a skin-like structure, wherein the (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating is sequentially divided into a FeNiMnCrV sputtering layer, a (FeNiMnCrV)Nx base layer, a CrN intermediate layer, a (FeNiMnCrV)Nx-CrN circulation layer, and a (FeNiMnCrV)Nx capping layer on the surface of a substrate material from bottom to top;
[0009] The (FeNiMnCrV)Nx base layer has an FCC phase structure with (111) and (200) as preferred orientations or an FCC phase structure with (200) as preferred orientation;
[0010] The CrN intermediate layer is a dense FCC phase structure;
[0011] The (FeNiMnCrV)Nx single layer in the (FeNiMnCrV)Nx-CrN circulation layer is an FCC phase structure with (111) and (200) as preferred orientations or an FCC phase structure with (200) as preferred orientation; the CrN single layer is an FCC phase structure;
[0012] The (FeNiMnCrV)Nx capping layer has an FCC phase structure with (200) as a preferred orientation.
[0013] The (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating provided by the present invention, wherein the (FeNiMnCrV)Nx capping layer is a FCC phase structure with dense grains and a preferred orientation of (200). The FCC phase structure with a preferred orientation of (200) has the most excellent H atom adsorption capacity and can effectively reduce the amount of H atoms diffusing downward. The next layer is a (FeNiMnCrV)Nx-CrN circulation layer. On the one hand, the interlayer interface formed by the circulation is used as a hydrogen trap to capture a large number of H atoms. In addition, the (FeNi The MnCrV)Nx single layer is an FCC phase structure with (111) and (200) as the preferred orientation or an FCC phase structure with (200) as the preferred orientation, which can adsorb H atoms well; the next one is a CrN intermediate layer with a dense structure. The CrN intermediate layer provides growth sites as a skeleton for stacking upwards. The complex interlayer interface can prevent the formation of columnar crystals and coarse grains, refine the grains, and improve the bearing capacity of the film layer; the next one is a FC with a dense structure with (111) and (200) as the preferred orientation. The (FeNiMnCrV)Nx base layer with a C phase structure or an FCC phase structure with (200) as a preferred orientation can provide a highly dense organizational structure; when the layers are stacked upward, the interface bonding can be significantly improved. Of course, the present invention also sets a FeNiMnCrV sputtering layer to increase the membrane-base bonding strength; in addition, taking the multi-layer structure hydrogen barrier coating as a whole, different energy barriers between interfaces are used to create hydrogen traps, so that most of the hydrogen is captured during the penetration process. The introduction of interlayer interfaces is very effective in improving the hydrogen barrier performance of the coating and can reduce the amount of infiltration into the structural material; and there is a significant potential energy difference at different positions, which produces a rough energy rugged landscape during hydrogen migration, which can greatly inhibit hydrogen migration, and utilizes the electronic interaction between hydrogen and different metal elements to lead to a significant local capture effect, which can limit its long-range transport, thereby preventing most hydrogen atoms from continuing to penetrate downward. Combining hydrogen absorption and hydrogen blocking will greatly reduce the hydrogen permeability. Taking the X70 substrate as an example, the X70 containing the above-mentioned coating makes the time for hydrogen to penetrate into the anode pool increase by nearly 10 compared with the bare X70 substrate without coating. 3 times.
[0014] The (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating provided by the present invention has a skin-like structure, wherein the (FeNiMnCrV)Nx capping layer effectively adsorbs H atoms, thereby reducing the flux of H atoms diffusing downward, similar to the stratum corneum of the skin, which as the outermost layer of the epidermis can help reduce water evaporation and absorb water to keep the skin moisturized. The (FeNiMnCrV)Nx-CrN circulation layer provides an interlayer interface as a hydrogen trap to capture a large number of H atoms, similar to the granular layer, which can serve as a barrier belt in the skin structure to resist the invasion of foreign objects. The CrN middle layer uses the dense FCC phase structure of CrN as a skeleton for upward stacking to provide growth sites, and the complex The interlayer interface can prevent the formation of columnar crystals and coarse grains, refine the grains, and improve the bearing capacity of the membrane layer, which is similar to the spinous layer with a similar morphological structure. In the spinous layer, there are many tiny particles in the cytoplasm. The particles contain glycoproteins, which can form tension filaments. These tension filaments pass through the granular cells and are connected to the connective tissue at the base, forming a connecting structure between the epidermis and the dermis; finally, the (FeNiMnCrV)Nx base layer has a highly dense tissue structure as the most important supporting structure, similar to the basal layer of the skin. The basal layer of the skin is the deepest layer of cells in the epidermis and is also where mother cells are produced. It is mainly composed of muscle fibers and connective tissue, providing support and elasticity for the skin.
[0015] In a preferred embodiment, the thickness of the (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating is 0.88-3 μm.
[0016] Further preferably, the thickness of the FeNiMnCrV sputtered layer is 20-30 nm;
[0017] The thickness of the (FeNiMnCrV)Nx base layer is 220-550nm;
[0018] The thickness of the CrN intermediate layer is 45-50 nm;
[0019] The thickness of the (FeNiMnCrV)Nx-CrN circulation layer is 265-1500nm, in the (FeNiMnCrV)Nx-CrN circulation layer, the thickness of the CrN single layer is 45-50nm, and the thickness of the (FeNiMnCrV)Nx single layer is 220-250nm;
[0020] The thickness of the (FeNiMnCrV)Nx capping layer is 330-660nm.
[0021] When the thickness of each layer is controlled within the above range, the final performance is excellent. If the thickness of the sputtered layer is too thick, it may affect the subsequent film growth mode, and if it is too thin, it may affect the film-base bonding strength. If the thickness of the (FeNiMnCrV)Nx base layer is too thin, it will also affect the subsequent bonding strength, resulting in poor performance. When the thickness of the (FeNiMnCrV)Nx-CrN circulation layer and the (FeNiMnCrV)Nx capping layer is controlled within the above range, H atoms can be best adsorbed and the hydrogen barrier performance is optimal.
[0022] The present invention also provides a method for preparing a skin-like structure (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating, wherein a FeNiMn alloy target, a pure chromium target, and a pure vanadium target are first etched on the surface of a substrate material under a vacuum environment by a multi-arc magnetic filtered cathode vacuum arc system to obtain a FeNiMnCrV sputtering layer, and then N2 is introduced to deposit a FeNiMn alloy target, a pure chromium target, and a pure vanadium target on the surface of the FeNiMnCrV sputtering layer to obtain a (FeNiMnCrV)Nx surface. A base layer is formed, and then a pure chromium target is used to deposit on the surface of the (FeNiMnCrV)Nx base layer to obtain a CrN intermediate layer. Subsequently, a FeNiMn alloy target, a pure chromium target, a pure vanadium target and a pure chromium target are alternately and cyclically deposited on the surface of the CrN intermediate layer to obtain a (FeNiMnCrV)Nx-CrN circulating layer. Finally, a FeNiMn alloy target, a pure chromium target and a pure vanadium target are deposited on the surface of the (FeNiMnCrV)Nx-CrN circulating layer to obtain a (FeNiMnCrV)Nx capping layer.
[0023] The solution of the present invention does not have too many restrictions on the material of the base material, such as silicon wafer, copper foil, carbon paper, steel or non-conductive polymer, etc.
[0024] In a preferred embodiment, the base material is made of steel, preferably 316L or 304 stainless steel. This preferred embodiment is based on the application of the hydrogen barrier coating of the present invention on the surface of pipelines and bottles in hydrogen environments, which are usually made of steel.
[0025] In a preferred embodiment, the roughness of the base material is 0.04-0.15.
[0026] Taking API X70 pipeline steel with a size of 40 × 40 × 1 mm as an example, in the actual operation process, its surface is first ground and polished to a surface roughness of 0.04~0.15, and then ultrasonically cleaned with acetone, ultrapure water and alcohol for 10 min respectively, and finally dried in a 60℃ oven for 2 h for use.
[0027] In a preferred embodiment, the FeNiMn alloy target material has the following composition, calculated by mass percentage: 15-25 wt.% iron, 15-25 wt.% nickel, and 50-70 wt.% manganese.
[0028] The inventors found that during the sputtering process, the FeNiMn alloy targets used all adopt the above-mentioned components, and then cooperate with pure chromium targets and pure vanadium targets to finally form a coating with excellent performance. If the composition of the target material is unreasonable, the coating may not even be obtained. For example, the FeNiMn alloy target, when the atomic ratio of Fe, Ni, and Mn is 1:1:1, may be affected by the overall magnetism of the mixed plasma in this system, or the size of the magnetic field in the magnetic filtration system, and it is impossible to start an arc stably and generate plasma.
[0029] Preferably, the purity of the FeNiMn alloy target is ≥99.95%, the purity of the pure chromium target is ≥99.80%, and the purity of the pure vanadium target is ≥99.80%.
[0030] The preferred solution is to etch the FeNiMn alloy target, pure chromium target and pure vanadium target on the surface of the substrate to obtain the FeNiMnCrV sputtering layer by adjusting the vacuum degree of the multi-arc magnetic filtered cathode vacuum arc system to 2.0~3.0×10 -3 Pa, and then set the arc head current corresponding to the FeNiMn alloy target to 45~70 A, the arc head current corresponding to the pure chromium target to 80~110 A, and the arc head current corresponding to the pure vanadium target to 70~90A, and then use bias voltages of -800V, -600V, -400V and -200V to etch for 30~45s respectively.
[0031] In the present invention, a relatively high bias voltage is first used to etch the substrate material to clean the surface of the substrate material, and then a bias voltage with slightly lower energy is gradually used to plate a layer of metal film to form a so-called pinning layer to increase the film-base bonding strength. The magnitude and time of the bias voltage are adjusted to obtain a FeNiMnCrV sputtering layer of a specific thickness. If the bias voltage is too large and the time is too long, defects such as pits may appear on the material surface. If the thickness is too thick, it may affect the subsequent film growth mode. If it is too thin, it may affect the film-base bonding strength.
[0032] The preferred scheme is to use FeNiMn alloy target, pure chromium target and pure vanadium target to deposit on the surface of FeNiMnCrV sputtering layer to obtain (FeNiMnCrV)Nx base layer by controlling the flow rate of N2 to 24~36 sccm, preferably 30-36 sccm, setting the current of the arc head corresponding to the FeNiMn alloy target to 45~70 A, the current of the arc head corresponding to the pure chromium target to 80~110A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V for deposition for 20~30min.
[0033] The inventors found that the flow rate of N2 has a great influence on the performance of the formed (FeNiMnCrV)Nx. When N is not contained, the resulting coating presents a coarse columnar crystal structure. As the N content increases, the grain size first decreases with the increase of the N content, and the crystal form first changes from a BCC structure to an amorphous structure, and then to an FCC phase structure with (111) and (200) as preferred orientations, and then to an FCC phase structure with (200) as preferred orientation until the nitrogen content reaches saturation. However, when the nitrogen content reaches saturation, the grain size begins to increase. In the range of 24~36 sccm, the grains are the smallest, and the crystal structure is an FCC phase structure with (111) and (200) as preferred orientations at low flow rates, and an FCC phase structure with (200) as preferred orientation at high flow rates.
[0034] During the deposition of the (FeNiMnCrV)Nx base layer, the bias voltage needs to be controlled. If it is too small (0V), the film-base bonding strength is not very good, and if it is higher than -150, the energy is too high and the film structure will be destroyed. In the actual operation, pre-flow nitrogen for about 30 seconds, wait until the vacuum in the chamber is stable, turn on the arc head power supply, and turn off the arc power supply after the deposition is completed.
[0035] Further preferably, before depositing the (FeNiMnCrV)Nx foundation layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system is controlled to 7~8×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 2~4×10 -3 Pa.
[0036] The preferred solution is to use a pure chromium target to deposit a CrN intermediate layer on the surface of a (FeNiMnCrV)Nx base layer. The process is as follows: control the N2 flow rate to 10-15 sccm, the arc head current corresponding to the pure chromium target to 90-110A, and then use a bias voltage of -100-150V for deposition for 10-15min.
[0037] By controlling the N2 flow rate within the above range, a dense FCC phase structure CrN intermediate layer can be formed. If the N2 flow rate is too small, the N element is insufficient and may not be able to completely react with Cr to form an amorphous structure, and the coating may not be dense enough.
[0038] Further preferably, before depositing the CrN intermediate layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system is stabilized at 3~4×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 1~2×10 -3 Pa.
[0039] The preferred scheme uses FeNiMn alloy target, pure chromium target, pure vanadium target and pure chromium target to alternately cyclically deposit on the surface of the CrN intermediate layer to obtain the (FeNiMnCrV)Nx-CrN cyclic layer. The process is as follows: first control the flow rate of N2 to 24~36sccm, preferably 30-36sccm, set the current of the arc head corresponding to the FeNiMn alloy target to 45~70A, the current of the arc head corresponding to the pure chromium target to 80~110A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V to deposit for 10~15min to obtain a (FeNiMnCrV)Nx single layer, and then adjust the flow rate of N2 to 10~15sccm, the current of the arc head corresponding to the pure chromium target to 90~110 A, then using a bias voltage of -100~-150V to deposit for 10~15min to obtain a CrN single layer, and alternately cyclically depositing for 1~5, preferably 3~5 cycles.
[0040] Further preferably, before depositing the (FeNiMnCrV)Nx monolayer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system is stabilized at 7~8×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 3~4×10 -3 Before depositing the CrN monolayer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was stabilized at 3~4×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 1~2×10 -3 Pa.
[0041] The preferred scheme is to use FeNiMn alloy target, pure chromium target and pure vanadium target to deposit the (FeNiMnCrV)Nx capping layer on the surface of the (FeNiMnCrV)Nx-CrN circulation layer. The process is as follows: control the flow rate of N2 to 36~48sccm, preferably 36~42sccm, set the current of the arc head corresponding to the FeNiMn alloy target to 45~70 A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V for deposition for 15~25min.
[0042] During the top layer process, the N2 flow rate needs to be controlled at 36~48sccm. Within this range, a denser FCC phase structure with (200) as the preferred orientation is obtained. The (200) FCC phase structure has the best H atom adsorption capacity. If the N2 flow rate is too low, the crystal structure is not a completely FCC phase structure with (200) as the preferred orientation or is an amorphous structure. When the N content is too high, the grain size increases and the coating density changes.
[0043] Further preferably, before depositing the (FeNiMnCrV)Nx capping layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system is stabilized at 7~9×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 3~5×10 -3 Pa.
[0044] The inventors found that the flow rate of N2 has a great influence on the performance of the formed (FeNiMnCrV)Nx. When N is not contained, the resulting coating presents a coarse columnar crystal structure. As the N content increases, the grain size first decreases with the increase of the N content, and the crystal form first changes from a BCC structure to an amorphous structure, and then to an FCC phase structure with (111) and (200) as preferred orientations, and then to an FCC phase structure with (200) as preferred orientation until the nitrogen content reaches saturation. However, when the nitrogen content reaches saturation, the grain size begins to increase. Therefore, the flow rate of N2 is controlled within the scope of the present invention to obtain a coating with fine, dense grains and preferred orientation. If the flow rate of N2 is too low, the internal disorder is high, forming an amorphous structure without complex H atom diffusion paths at grain boundaries. If the N content in the coating is high, the grain size increases and the density of the coating changes.
[0045] Principles and advantages
[0046] The (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating provided by the present invention has a skin-like structure, in which a high entropy nitride is used as a capping layer, and there is a sufficiently significant atomic size difference in the layer to cause severe lattice distortion, and the grains are dense and have an FCC phase structure with a preferred orientation of (200). The FCC phase structure with a preferred orientation of (200) has the most excellent H atom adsorption capacity, which effectively reduces the flux of H atoms diffusing downward. The (FeNiMnCrV)Nx-CrN circulation layer provides an interlayer interface as a hydrogen trap to capture a large number of H atoms. The CrN intermediate layer uses the dense FCC phase structure of CrN as a skeleton for stacking upward to provide a growth site. Finally, the (FeNiMnCrV)Nx base layer is very dense and has good crystallinity, which helps to provide a good bottom environment for the subsequent deposition of thin films. In addition, from the overall perspective of the multilayer structure, different energy barriers between interfaces are used to create hydrogen traps, so that most of the hydrogen is captured during the penetration process. The coating composed of multilayer thin films has high hydrogen penetration barrier performance. The introduction of interlayer interfaces is very effective in improving the hydrogen barrier performance of the coating and can reduce the amount of infiltration into the structural material. In addition, there is a significant potential energy difference at different positions, which produces a rough energy rugged landscape during hydrogen migration, which can greatly inhibit hydrogen migration. In addition, the electronic interaction between hydrogen and different metal elements is used to produce a significant local capture effect, which can limit its long-range hydrogen transport, thereby preventing most hydrogen atoms from continuing to penetrate downward. Combining hydrogen absorption and hydrogen barrier will greatly reduce the hydrogen permeability. Taking the X70 substrate as an example, the X70 containing the above coating makes the time for hydrogen to penetrate into the anode pool increase by nearly 10 compared with the bare X70 substrate without coating. 3 times.
[0047] The hydrogen barrier composite coating of the present invention adopts multi-arc magnetic filtering cathode vacuum arc technology, and the prepared (FeNiMnCrV)Nx can effectively regulate the crystal structure, preferential orientation and grain size of the coating, enhance the film-base bonding strength, the density of the coating and reduce defects, thereby improving the hydrogen barrier performance of the composite coating.
[0048] The preparation method of the hydrogen barrier coating of the skin-like (FeNiMnCrV)Nx multilayer structure prepared on the substrate of the present invention is simple to operate, has a low preparation cost, and has a more uniform coating, and can effectively improve the hydrogen barrier performance and service performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a design drawing of the (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating involved in the present invention.
[0050] Figure 2 This is a SEM image of the (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating prepared in Example 1 of the present invention.
[0051] Figure 3 is the cross-sectional SEM image of the prepared (FeNiMnCrV)Nx single layer, where Figure 3 (A) is S-30sccm prepared with a nitrogen flow rate of 30sccm, Figure 3 (B) is S-36sccm prepared with a nitrogen flow rate of 36sccm.
[0052] Figure 4 The graph is a current-time hydrogen permeation curve of the hydrogen barrier coating obtained in the embodiment and the comparative example. DETAILED DESCRIPTION
[0053] The preparation of the skin-like (FeNiMnCrV)Nx multilayer hydrogen barrier coating structure of the present invention is further described below through specific examples.
[0054] Example 1
[0055] In this example, the skin-like structure (FeNiMnCrV) Nx multilayer hydrogen barrier coating on the surface of the pipeline steel is applied to the surface of API X70 pipeline steel. The preparation steps are as follows:
[0056] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0057] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0058] 3. Before deposition, the vacuum degree in the chamber is controlled at 2.5× 10 -3 Pa. During the etching process, the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60A, 80A and 75A, respectively, and then etched on the X70 substrate at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s, respectively, without external heating of the substrate. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0059] 4. Set the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10-3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A, respectively. The deposition was carried out on the surface of X70 pipeline steel at a bias voltage of -100 V for 30 min. During the deposition process, the nitrogen flow rate was adjusted to stabilize the vacuum degree at 3.6×10 -3 Pa, a dense (FeNiMnCrV)Nx layer was obtained, marked as HEN as the "foundation" layer, and the arc power was turned off after the deposition was completed.
[0060] 5. Reduce the N2 gas flow rate to 10 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 3.6×10 -3 At this time, the power supply of the Cr arc head was turned on, the current was set to 90 A, the deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 1.7×10 -3 Pa, a CrN layer with a thickness of about 45 nm is deposited on the obtained HEN layer as an intermediate layer, and the arc current is turned off after the deposition is completed.
[0061] 6. Adjust the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 3.6×10 -3 Pa, and deposit a layer of S-30sccm layer with a thickness of about 220 nm on the obtained CrN layer as a cycle layer. After the deposition is completed, the arc current is turned off. The CrN layer and the S-30sccm layer are taken as one cycle, and the cycle is repeated for 5 cycles.
[0062] 7. Finally, adjust the N2 gas flow rate to 36 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 8.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 25 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 4.2×10 -3 Pa, and deposit another layer of S-36 sccm layer with a thickness of 570 nm on the original 5-cycle period layer as a capping layer. After the deposition is completed, the arc current is turned off.
[0063] Figure 2This is an SEM image of the (FeNiMnCrV)Nx multilayer structure prepared in Example 1. It can be seen from the figure that the total thickness of the coating in the figure is 2.71μm, wherein the thickness of the (FeNiMnCrV)Nx base layer (nitrogen flow rate is 30sccm, S-30sccm) is 784nm, the (darker layer) is the CrN layer, the thickness is 45nm, the top is the (FeNiMnCrV)Nx capping layer (nitrogen flow rate is 36sccm, S-36sccm) with a thickness of 570nm, and between the (FeNiMnCrV)Nx capping layer and the CrN layer is the (FeNiMnCrV)Nx-CrN circulation layer. From the overall perspective, clear interfaces between the layers can be seen, and the coating structure is complete, with high density and no obvious visible defects.
[0064] To clearly see the (FeNiMnCrV)Nx formed when the nitrogen flow rate is 30sccm and the nitrogen flow rate is 36sccm, Figure 3 The cross-sectional SEM images of (A) S-30sccm and (B) S-36sccm single layers are given. From the images, it can be seen that the grains are very small and dense, among which S-30sccm has a FCC phase structure with (111) and (200) preferential orientations, and S-36sccm has a FCC phase structure with (200) preferential orientations.
[0065] Example 2
[0066] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0067] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0068] 3. Before deposition, the vacuum degree in the chamber is controlled at 2.7× 10 -3Pa. During the etching process, the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60A, 80A and 75A, respectively, and then etched on the X70 substrate at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s, respectively, without external heating of the substrate. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0069] 4. Set the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A, respectively. The deposition was carried out on the surface of X70 pipeline steel at a bias voltage of -100 V for 20 min. During the deposition process, the nitrogen flow rate was adjusted to stabilize the vacuum degree at 3.6×10 -3 Pa, a dense (FeNiMnCrV)Nx layer was obtained, marked as HEN as the "foundation" layer, and the arc power was turned off after the deposition was completed.
[0070] 5. Reduce the N2 gas flow rate to 10 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 3.6×10 -3 At this time, the power supply of the Cr arc head was turned on, the current was set to 90 A, the deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 1.7×10 -3 Pa, a CrN layer with a thickness of about 45 nm is deposited on the obtained HEN layer as an intermediate layer, and the arc current is turned off after the deposition is completed.
[0071] 6. Adjust the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 3.6×10 -3 Pa, and deposit a layer of S-30sccm layer with a thickness of about 220 nm on the obtained CrN layer as a cycle layer. After the deposition is completed, the arc current is turned off. The CrN layer and the S-30sccm layer are taken as one cycle, and the cycle is repeated for 3 cycles.
[0072] 7. Finally, adjust the N2 gas flow rate to 36 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 8.6×10-3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 15 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 4.2×10 -3 Pa, and deposit a S-36sccm layer with a thickness of about 330 nm as a capping layer on the original 3-cycle period layer. After the deposition is completed, the arc current is turned off, and the thickness of the multi-layer hydrogen barrier coating is about 1.55 μm.
[0073] Comparative Example 1
[0074] The difference between the comparative example 1 and the embodiment 1 is that the comparative example 1 does not prepare the "top layer":
[0075] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0076] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0077] 3. Before deposition, the vacuum degree in the chamber was controlled at 3.0× 10 -3 Pa. During the etching process, the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60A, 80A and 75A, respectively, and then etched on the X70 substrate at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s, respectively, without external heating of the substrate. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0078] 4. Set the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A, respectively. The deposition was carried out on the surface of X70 pipeline steel at a bias voltage of -100 V for 30 min. During the deposition process, the nitrogen flow rate was adjusted to stabilize the vacuum degree at 3.6×10 -3 Pa, a dense (FeNiMnCrV)Nx layer was obtained, marked as HEN as the "foundation" layer, and the arc power was turned off after the deposition was completed.
[0079] 5. Reduce the N2 gas flow rate to 10 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 3.6×10 -3 At this time, the power supply of the Cr arc head was turned on, the current was set to 90 A, the deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 1.7×10 -3 Pa, a CrN layer with a thickness of about 45 nm is deposited on the obtained HEN layer as an intermediate layer, and the arc current is turned off after the deposition is completed.
[0080] 6. Adjust the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 3.6×10 -3 Pa, and a layer of S-30sccm layer with a thickness of about 220 nm is deposited on the obtained CrN layer as a cycle layer, and the arc current is turned off after the deposition is completed. The CrN layer and the S-30sccm layer are used as a cycle, and 5 cycles are cycled. After the deposition is completed, the arc current is turned off, and the thickness of the multilayer hydrogen barrier coating is about 1.5 μm.
[0081] Comparative Example 2
[0082] The difference between the comparative example 2 and the example 1 is that the comparative example 2 does not prepare the "base layer":
[0083] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0084] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0085] 3. Before deposition, the vacuum degree in the chamber is controlled at 2.4× 10 -3 Pa. During the etching process, the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60A, 80A and 75A, respectively, and then etched on the X70 substrate at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s, respectively, without external heating of the substrate. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0086] 4. Set the N2 gas flow rate to 10 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 3.6×10 -3 At this time, the power supply of the Cr arc head was turned on, the current was set to 90 A, the deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 1.7×10 -3 Pa, a CrN layer with a thickness of about 45 nm is deposited on the obtained X70 substrate, and the arc current is turned off after the deposition is completed.
[0087] 5. Adjust the N2 gas flow rate to 30 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 7.6×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 10 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 3.6×10 -3 Pa, and then deposit a layer of S-30sccm layer with a thickness of about 220 nm on the obtained CrN layer as a cycle layer. After the deposition is completed, the arc current is turned off. The CrN layer and the S-30sccm layer are taken as one cycle, and the cycle is repeated for 5 cycles.
[0088] 6. Finally, adjust the N2 gas flow rate to 36 sccm, pre-flow nitrogen for about 30 s, and stabilize the pressure in the chamber at 8.6×10 -3At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A respectively. The deflection voltage was -100 V, the deposition time was 25 min, and the nitrogen flow rate was adjusted during the deposition process to keep the vacuum degree at 4.2×10 -3 Pa, and deposit a S-36sccm layer with a thickness of about 550 nm on the original 5-cycle layer as a capping layer. After the deposition is completed, the arc current is turned off, and the thickness of the multi-layer hydrogen barrier coating is about 2.55 μm.
[0089] Comparative Example 3
[0090] The difference between the comparative example 3 and the embodiment 1 is that the comparative example 3 does not undergo stratification treatment:
[0091] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0092] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0093] 3. Before deposition, the vacuum degree in the chamber is controlled at 2.5× 10 -3 Pa. During the etching process, the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60A, 80A and 75A, respectively, and then etched on the X70 substrate at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s, respectively, without external heating of the substrate. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0094] 4. Set the N2 gas flow rate to 36 sccm, pre-flow nitrogen for about 30 s, and stabilize the vacuum degree in the chamber at 8.2×10 -3 At this time, the power supplies of the three arc heads of FeNiMn, Cr and V were turned on, and the currents were set to 60, 80 and 75 A, respectively. The deposition was carried out on the surface of X70 pipeline steel at a bias voltage of -100 V for 60 min. During the deposition process, the nitrogen flow rate was adjusted to stabilize the vacuum pressure at 3.6×10-3 Pa, a dense (FeNiMnCrV)Nx layer is obtained, and the arc current is turned off after the deposition is completed. The thickness of the multi-layer hydrogen barrier coating is about 1.593 μm.
[0095]
[0096] Finally, it should be noted that the above examples are only specific implementation examples of the present invention. Obviously, the present invention is not limited to the above implementation examples, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating, characterized in that: The (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating is divided into a FeNiMnCrV sputtering layer, a (FeNiMnCrV)Nx base layer, a CrN intermediate layer, a (FeNiMnCrV)Nx-CrN circulation layer, and a (FeNiMnCrV)Nx capping layer from bottom to top on the surface of the substrate material; The (FeNiMnCrV)Nx base layer has an FCC phase structure with (111) and (200) as preferred orientations or an FCC phase structure with (200) as preferred orientation; The CrN intermediate layer is of FCC structure; The (FeNiMnCrV)Nx single layer in the (FeNiMnCrV)Nx-CrN circulation layer has an FCC phase structure with (111) and (200) as preferred orientations or an FCC phase structure with (200) as preferred orientation; the CrN single layer has an FCC phase structure; The (FeNiMnCrV)Nx capping layer has an FCC phase structure with (200) as a preferred orientation.
2. The skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 1, characterized in that: The thickness of the (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating is 0.88-3 μm.
3. A skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 1 or 2, characterized in that: The thickness of the FeNiMnCrV sputtered layer is 20-30 nm; The thickness of the (FeNiMnCrV)Nx base layer is 220-800nm The thickness of the CrN intermediate layer is 45-50 nm; The thickness of the (FeNiMnCrV)Nx-CrN circulation layer is 265-1500nmnm, in the (FeNiMnCrV)Nx-CrN circulation layer, the thickness of the CrN single layer is 45-50nm, and the thickness of the (FeNiMnCrV)Nx single layer is 220-250nm; The thickness of the (FeNiMnCrV)Nx capping layer is 330-660nm.
4. A method for preparing a skin-like structured (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to any one of claims 1 to 3, characterized in that: Through a multi-arc magnetic filtered cathode vacuum arc system, in a vacuum environment, FeNiMn alloy target, pure chromium target and pure vanadium target are first etched on the surface of the base material to obtain a FeNiMnCrV sputtering layer, and then N2 is introduced, and FeNiMn alloy target, pure chromium target and pure vanadium target are first deposited on the surface of the FeNiMnCrV sputtering layer to obtain a (FeNiMnCrV)Nx base layer, and then a pure chromium target is deposited on the surface of the (FeNiMnCrV)Nx base layer to obtain a CrN intermediate layer, and then FeNiMn alloy target, pure chromium target, pure vanadium target and pure chromium target are alternately and cyclically deposited on the surface of the CrN intermediate layer to obtain a (FeNiMnCrV)Nx-CrN circulating layer, and finally FeNiMn alloy target, pure chromium target and pure vanadium target are deposited on the surface of the (FeNiMnCrV)Nx-CrN circulating layer to obtain a (FeNiMnCrV)Nx capping layer.
5. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The material of the base material is steel; The roughness of the base material is 0.04-0.15; The FeNiMn alloy target material has the following composition by mass percentage: 15-25 wt.% iron, 15-25 wt.% nickel, and 50-70 wt.% manganese.
6. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The process of etching the FeNiMn alloy target, pure chromium target and pure vanadium target on the surface of the substrate to obtain the FeNiMnCrV sputtering layer is as follows: the vacuum degree of the multi-arc magnetic filtered cathode vacuum arc system is adjusted to 2.0~3.0×10 -3 Pa, and then set the arc head current corresponding to the FeNiMn alloy target to 45~70 A, the arc head current corresponding to the pure chromium target to 80~110 A, and the arc head current corresponding to the pure vanadium target to 70~90A, and then use bias voltages of -800V, -600V, -400V and -200V to etch for 30~45s respectively.
7. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The process of using FeNiMn alloy target, pure chromium target and pure vanadium target to deposit on the surface of FeNiMnCrV sputtering layer to obtain (FeNiMnCrV)Nx base layer is as follows: control the flow rate of N2 to 24~36 sccm, set the current of the arc head corresponding to the FeNiMn alloy target to 45~70 A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V to deposit for 20~30min; Before depositing the (FeNiMnCrV)Nx foundation layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to 7~8×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 2~4×10 - 3 Pa.
8. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The process of using pure chromium target to deposit CrN intermediate layer on the surface of (FeNiMnCrV)Nx base layer is as follows: control the flow rate of N2 to 10~15 sccm, the current of the arc head corresponding to the pure chromium target to 90~110A, and then use a bias voltage of -100~-150V to deposit for 10~15min; Before depositing the CrN intermediate layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was stabilized at 3~4×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 1~2×10 -3 Pa.
9. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The process of using FeNiMn alloy target, pure chromium target, pure vanadium target and pure chromium target to alternately and cyclically deposit on the surface of CrN intermediate layer to obtain (FeNiMnCrV)Nx-CrN cyclic layer is as follows: first, the flow rate of N2 is controlled to 24-36 sccm, the current of the arc head corresponding to the FeNiMn alloy target is set to 45-70 A, the current of the arc head corresponding to the pure chromium target is set to 80-110 A, and the current of the arc head corresponding to the pure vanadium target is set to 75-90A, and then a bias voltage of 0V-150V is used to deposit for 10-15min to obtain a (FeNiMnCrV)Nx single layer, and then the flow rate of N2 is adjusted to 10-15 sccm, the current of the arc head corresponding to the pure chromium target is set to 90-110A, and then a bias voltage of -100-150V is used to deposit for 10-15min to obtain a CrN single layer, and the alternate cyclic deposition is performed for 1-5 cycles; Before depositing the (FeNiMnCrV)Nx monolayer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled at 7~8×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 3~4×10 -3 Before depositing the CrN monolayer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was stabilized at 3~4×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 1~2×10 -3 Pa.
10. The method for preparing a skin-like (FeNiMnCrV)Nx multilayer structure hydrogen barrier coating according to claim 4, characterized in that: The process of depositing the (FeNiMnCrV)Nx capping layer on the surface of the (FeNiMnCrV)Nx-CrN circulation layer using FeNiMn alloy target, pure chromium target and pure vanadium target is as follows: control the flow rate of N2 to 36-48sccm, set the current of the arc head corresponding to the FeNiMn alloy target to 45-70 A, the current of the arc head corresponding to the pure chromium target to 80-110 A, and the current of the arc head corresponding to the pure vanadium target to 75-90A, and then use a bias voltage of 0V~-150V for deposition for 15-25min; Before depositing the (FeNiMnCrV)Nx capping layer, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was stabilized at 7~9×10 -3 During the deposition process, the vacuum degree in the multi-arc magnetic filtered cathode vacuum arc system was controlled to be 3~5×10 -3 Pa.
